2013
DOI: 10.1177/1071100713487527
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Reconstruction of Peroneal Tendons

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…No studies were found with the primary focus on rehabilitation of surgically treated peroneal tendon tears or ruptures. Included studies described their rehabilitation method after one or more of the following surgical treatment methods: group A: primary repair with or without tubularization of the tendon, [ 1 , 2 , 6 , 7 , 12 14 , 19 , 23 – 28 , 31 , 36 , 39 , 43 , 47 50 , 53 , 56 , 61 , 62 , 65 , 69 ] group B: tenodesis, [ 1 , 2 , 4 , 5 , 10 , 14 , 16 , 25 , 30 , 40 , 43 , 44 , 46 , 47 , 49 , 50 , 61 , 62 , 67 , 69 ] group C: grafting [ 8 , 10 , 21 , 29 , 34 , 37 , 38 , 42 , 43 , 45 , 46 , 49 , 50 , 61 , 69 ] and group D: end-to-end suturing [ 1 , 29 , 41 , 43 , 47 , 66 , 68 ]. Fourteen studies reported two or more surgical treatment methods [ 10 , 25 , 29 , 43 , 4...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies were found with the primary focus on rehabilitation of surgically treated peroneal tendon tears or ruptures. Included studies described their rehabilitation method after one or more of the following surgical treatment methods: group A: primary repair with or without tubularization of the tendon, [ 1 , 2 , 6 , 7 , 12 14 , 19 , 23 – 28 , 31 , 36 , 39 , 43 , 47 50 , 53 , 56 , 61 , 62 , 65 , 69 ] group B: tenodesis, [ 1 , 2 , 4 , 5 , 10 , 14 , 16 , 25 , 30 , 40 , 43 , 44 , 46 , 47 , 49 , 50 , 61 , 62 , 67 , 69 ] group C: grafting [ 8 , 10 , 21 , 29 , 34 , 37 , 38 , 42 , 43 , 45 , 46 , 49 , 50 , 61 , 69 ] and group D: end-to-end suturing [ 1 , 29 , 41 , 43 , 47 , 66 , 68 ]. Fourteen studies reported two or more surgical treatment methods [ 10 , 25 , 29 , 43 , 4...…”
Section: Resultsmentioning
confidence: 99%
“…Rehabilitation after surgical treatment with grafting was reported in 16 studies [ 8 , 10 , 21 , 29 , 34 , 37 , 38 , 42 , 43 , 45 , 46 , 47 , 49 , 50 , 61 , 69 ] with a median immobilization period of 6.3 (range 3.0–13) weeks (Table 2 ). Of the studies ( n = 15) that reported on the start of ROM, 7 studies (47 %) reported on a start within 4 weeks post-operative [ 10 , 34 , 45 47 , 61 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several surgical procedures to repair tendon ruptures are reported in the literature, yet no clear consensus on the best technique or rehabilitative protocol exists. [1,3,11] Based on the severity of peroneal tendon rupture (e.g., partial-thickness split versus full-thickness split), treatment protocols vary from conservative treatment—including rest, ice, compression, and elevation—to invasive or percutaneous surgical repair. [12] While surgical repair has proven to be effective, it has been reported that as many as 25.4% of patients struggle with post-op complications such as pain, and 17.4% experience persistent swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Peroneal tendon injuries are associated with debilitating complications—such as chronic ankle instability, foot deformities, chronic pain, and bone spurs [1] —thus, prompt diagnosis and repair are crucial for optimizing clinical outcomes. Initially, pain levels contribute to extended lengths of post-operative (post-op) rehabilitation while development of tissue adhesions and fibrosis limit long-term functionality through reduced range of motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation